You are on page 1of 5


The product rule

Suppose u and v are functions, and u0 and v 0 are their derivatives. The product rule says that (uv )0 = uv 0 + u0 v Why is this true? First we show that, if c is a constant, then (cv )0 = cv 0 . That s because if you multiply a function by a constant, then any change in the function, and hence the rate of change of the function, gets multiplied by that constant. We could also appeal directly to local linearity. The derivative of a function at a point is the slope of the straight line that the graph of the function looks like at that point. If you multiply a linear function f (x) = mx + b by a constant c, you get cf (x) = cmx + cb, so you have multiplied the slope m by c. What about the general product rule? If u and v are both changing, then there are two contributions to the change in uv , one from the change in u and the other from the change in v . If u were not changing, then u would be a constant, and (uv )0 would equal uv 0 . Similarly, if v were a constant, then (uv )0 would be u0 v . Because u and v are both changing, we have to add uv 0 and u0 v to get the total rate of change.

The quotient rule

u 0 u0 v uv 0 = v v2 follows directly from the product rule. Dierentiate both sides of the straightforward equation u v=u v using the product rule to get u 0 u v + v 0 = u0 v v 0 and then solve for (u=v ) getting u 0 0 v 0 0 u 0 u v = u v uv = v v v2

The quotient rule

The power rule

(un )0 = nun 1 u0

We will illustrate why the power rule

is true by looking at the case n = 4. So we want to compute the derivative of u4 . There are four factors of u, each of which is changing. If we vary each one separately, keeping the others constant, and use the constant-multiple rule, we get the four terms u0 u u u u u0 u u u u u0 u u u u u0

depending on which u is allowed to vary. These terms add up to 4u3 u0 , as advertised. This shows why the power rule holds for any positive integer n. It also holds for fractions and negative numbers. For example, to compute the 2 derivative of u1=2 , we use the fact that u1=2 = u. Dierentiating both 0 sides, using the power rule for n = 2 on the left, gives 2u1=2 u1=2 = u0 so 0 u 1=2 u0 , like it s supposed to. u1=2 = 1 2

The trigonometric functions

What are the derivatives of sin t and cos t? Look at the gure below where O = (0; 0) and A = (1; 0), so the length of the line OA is 1. We have drawn a piece of the circle of radius 1 and center O. It goes from A to P and beyond. The angle t at O is equal to the length of the arc from A to P because we measure angles in radians. If we let (x; y ) be the coordinates of P , then x = cos t and y = sin t. We have also drawn a line from P parallel to the x-axis. This line makes an angle of t with the radius OP the mantra here is alternate interior angles . Now put another point Q on the circle, a little above P , so that the arc from P to Q has a very small length dt. Draw a perpendicular line down from Q.

Q dt P t

t O A

As a circle is a smooth curve, and dt is extremely small, we can treat the arc from P to Q as if it were a straight line. The angle at the top of the small triangle (at the vertex Q) is equal to t because it is the complement of the angle at the right of the small triangle (at the vertex P ), and that angle is the complement of t because the radius OP of the circle is perpendicular to the circle. The left side of the triangle has length dy and the bottom has length dx (because x decreases as you go from P to Q). Looking at the trigonometric relations in the small right triangle, we see that cos t = dx dy and sin t = . dt dt

That is, the derivative of y = sin t is cos t, and the derivative of x = cos t is sin t.

The exponential function

For any a > 0 we have the function ax . Below are the plots of the functions 1:5x , 2x , 2:5x , and 3x .






The function ex , or exp x, is dened as that function ax whose graph has slope 1 at (0; 1); that is, the derivative of ex is 1 when x = 0. Now let u (x) = ex and v (x) = u (x + c) for any constant c. Note that u0 (0) = 1. The graph of v is simply the graph of u shifted horizontally by c. As slopes are preserved when you shift a graph, we have v 0 (0) = u0 (c). On the other hand, the law of exponents tells us that v = ec u, so the constantmultiple rule tells us that v 0 = ec u0 , whence v 0 (0) = ec u0 (0) = ec . That is, u0 (c) = v 0 (0) = ec , which is true no matter what c is. So u0 = u, that is to say, the derivative of ex is ex .

The logarithm function

The (natural) logarithm function, ln x, is dened by the fact that y = ln x exactly when x = ey . Dierentiating the second equation with respect to y , we get dx = ey dy So dy 1 1 = y = dx e x which says that the derivative of y = ln x is 1=x.

Inverse trigonometric functions

The function arctan x, also written as tan 1 x, has the property that if y = tan 1 x, then x = tan y . Since x = tan y = sin y= cos y , we can use the quotient rule to see that cos y cos y (sin y ) ( sin y ) dx = = 1 + tan2 y = 1 + x2 dy cos2 y So, if y = arctan x, then dy 1 = dx 1 + x2 a remarkable formula because it is clean and doesn t involve trigonometric functions. If y = arcsin x, then x = sin y and =2 y =2. So q p dx = cos y = 1 sin2 y = 1 x2 dy and we see that if y = arcsin x, then 1 dy =p dx 1 x2

The chain rule

dy dy dx = dt dx dt

If y is a function of x, and x is a function of t, then

You can think of this formula as being true because you can cancel the two dx s on the right. As an example, what is the derivative of y = sin 2t? We can set x = 2t, whereupon y = sin x. We see that dx=dt = 2 and dy=dx = cos x, so dy=dt = (cos x) 2 = 2 cos x = 2 cos 2t.